Double jeopardy! political correctness in kiddie lit and the popular media - Diaz de Rivera, Lina B. (The RAP Journal, 2010)
This paper examines compliance with the dictates of political correctness in print and popular media for children by citing some national and international children's books and cartoons plus offerings on television and the movies. It is written in the light of the classification of the "binary poles" of power identified by structuralist criticism in the field of letters. Although the feminist movement and the black revolution have significantly accomplished much as regards their causes particularly in the west, it is noted that the child's domain has not equally received the same attention. The paper cites some random samples of what the community of writers, cartoonist, and movie and TV producers have done so far to pay more than a lip service to improve the attitudes toward-and to show deference to-the reader, viewer and consumer who is a child.